The role of parenthood in worry about overheating in homes in the UK and the US and implications for energy use: An online survey study. - Gesche M Huebner (PLoS ONE, 2022)
Climate change brings an increase in temperatures and a higher frequency of heatwaves. Both have been linked to a rise in suicide rates and violent crime on a population level. However, little is known about the link between mental health and ambient temperatures on an individual level and for particular subgroups. Overheating poses health risks to children and disturbs sleep; leading to the expectation that parents are more worried about their homes getting too hot than non-parents. Two online survey studies (N = 1000 each) were conducted in the UK and the US to understand to what extent parents and an age-matched comparison group without children are worried about overheating and how they differ in their mitigation actions. Findings did not support the main hypotheses around greater overheating worry amongst parents in general, mothers or those with very young children. However, parents indicated a greater likelihood to upgrade or install air-conditioning (US) and to get electric fans (UK). Parents in the UK indicated using more mitigation options to cope with overheating than non-parents. Parents in the US, whilst not reporting doing more actions, were more likely to use air-conditioning to deal with overheating than non-parents. Finally, those parents who mentioned health impacts on children as a reason for worry about overheating, were more concerned about overheating than parents who had other reasons than children's health as a reason for being concerned about overheating. In summary, parental status might have implications for cooling energy use and concern for children's health might increase overheating worry; however, many open questions remain.